Highly efficient wearable CPW antenna enabled by EBG-FSS structure for medical body area network applications - Ashyap, Adel Y. I.; Abidin, Zuhairiah Zainal; Dahlan, Samsul Haimi; Majid, Huda A.; Kamarudin, Muhammad Ramlee; Alomainy, Akram; Abd-Alhameed, Raed A.; Kosha, Jamal Sulieman; Noras, James M. (IEEE, 2018)
A wearable fabric CPW antenna is presented for medical body area network (MBAN) applications at 2.4 GHz based on an electromagnetic bandgap design and frequency selective surface (EBG-FSS). Without EBG-FSS, the basic antenna has an omnidirectional radiation pattern, and when operated close to human tissue, the performance and efficiency degrade, and there is a high specific absorption rate. To overcome this problem, the antenna incorporates EBG-FSS, which reduces the backward radiation, with SAR reduced by 95%. The gain is improved to 6.55 dBi and the front-to-back ratio is enhanced by 13 dB compared to the basic antenna. The overall dimensions of the integrated design are 60×60×2.4 mm 3 . Simulation and experimental studies reveal that the antenna integrated with EBG-FSS can tolerate loading by human tissue as well as bending. Thus, the design is a good candidate for MBAN applications.